Cluster-cooperative model of territory development (on the example of Kharkiv region) - Polusmiak, Yuliia; Masiuk, Veronika (Management and Entrepreneurship: Trends of Development, 2022)
The article is aimed on studying of the essence of clustering, considerating of the importance of the synergistic effect that appears through cooperation of enterprises in the leading industries of Ukraine. The Kharkiv region is an example of effective cooperation within certain organizations. This territory of Ukraine had high development indicators in the pre-war period. In our time, it is necessary to analyze the past experience, advantages, disadvantages and achievements of previously existing associations and organizations, which, due to hostilities, suspended their activities, in order to begin the reconstruction of the country. The purpose of the article is to answer a question: «why the cooperation of firms and organizations is more effective than the functioning of individual enterprises?»; to focus attention on identification of the modern meaning, motivations of use of clusters by business entities. Also, in the article is defined the concept of «clusterization», the influence of cooperations on the competitiveness of organizations is considered, the leading industries of Ukraine are reviewed and the analysis of the activity of alliances is available. Some problems of innovative activity in Ukraine are also considered. Methodology: descriptive, theoretical methods and statistical data were used in the research. As a result of the research, the shortcomings of the policy in the field of innovative activity were mentioned, the conclusions were formed regarding the chosen topic. JEL Classification: O14, O18.